Three novel 4-methylcoumarin derivatives - Ćavar, Sanja; Kovač, Franci (Bulletin of Chemists and Technologists of Bosnia and Herzegovina, 2012)
Substituted 4-methylcoumarins are synthesized from phenols and ethyl acetoacetate via Pechmann condensation, then, using common method for benzoylation, three novel coumarin derivatives were obtained: 4-methyl-2-oxo-2H-chromen-6-yl benzoate (2a), 4,5-dimethyl-2-oxo-2H-chromen-7-yl benzoate (2b), and 4-methyl-2-oxo-2H-chromen-7,8-diyl benzoate (2c). The structures of novel coumarins were characterized by elemental analysis, GC/MS, NMR, and IR techniques.